STRATEGI PENINGKATAN KUALITAS PELAYANAN PUBLIK DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN INDRAGIRI HILIR - Multazam Multazam; Abdul Sadad (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
This research was conducted to find out how the implementation of strategies and obstacles faced by the Office of Investment and One Stop Services in Indragiri Hilir Regency in improving the quality of public services. The theory used in this study from Osborne and Plastrik which suggests that there are several strategies for providing public services that can be applied to government organizations to improve service quality, which are then called the Five C's, namely: Core Strategy, Consequences Strategy. Customer Strategy (Customer strategy), Control Strategy (Control Strategy), and Culture Strategy (Cultural Strategy). The research technique was carried out using qualitative data analysis techniques with a case study approach and the necessary data were collected through interviews, observations and documentation, which were then analyzed using interactive model data according to Miles and Huberman. The results of this study indicate that the efforts made by the Office of Investment and One Stop Integrated Services of Indragiri Hilri Regency in improving the quality of public services using the five C'S strategy have not been optimal enough because there are factors that hinder the implementation of this strategy, namely inadequate infrastructure and resources.